78: IMPACT OF DECISION AIDS IN PROSTATE CANCER SCREENING: A SYSTEMATIC REVIEW AND META-ANALYSIS. (8th February 2017) - Arab-Zozani, Morteza; Vahdatimanesh, Zahra; Kakemam, Edris; Sokhanvar, Mobin; Ghoddosineghad, Djavad; Hasanpoor, Edris
Abstract : Background and aims: Patient Decision Aids are specially designed information resources that help people make decisions about difficult healthcare options. The aim of this review was to examine the impact of decision aids in patients with prostate cancer screening. Methods: Embase, PubMed and the Cochrane Central Register of Controlled Trials (CENTRAL) and reference list of the included studies were searched without year and language restriction through July 2016. Two independent reviewers checked studies for quality and eligibility and finally extracted the data. We used comprehensive meta-analysis software version 2 (CMA 2.0) for analysing the data. Results: Seven randomized controlled trials and well-designed quasi-experimental studies with total number of 5195 were included in the meta-analysis. The quality of included studies was faired. The overall mean quality score for the 7 included studies was 3.2 out of 5 (SD=0.87). Decision aids show better impact on decrease interest in prostate-specific antigen testing and screening behaviour among patients seeking routine care (M-H RR 0.59, 95% CI 0.41 to 0.76), proportion of people who were passive in decision making (M-H RR 0.76, 95% CI 0.60 to 0.96) and proportion of people who remained undecided post-intervention (M-H RR 0.66, 95% CI 0.43 to 0.84). Conclusion: According to the results, decision Aids resulted in significant benefit over usual care in patients with prostate cancer screening.